Changing the news: A media engagement toolkit for Aboriginal health professionals - Leach, V.; James, R.; McManus, Alexandra; Thompson, S. (Health communication resources limited, 2013)
To guide Aboriginal health professionals who initiate contact with the media or to respond to journalists seeking a comment or story.